ANALISIS KESULITAN SISWA DALAM MANAJEMEN WAKTU BELAJAR DAN KEGIATAN ASRAMA KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Assifa Nur Azizah; Dede Indra Setiabudi; Iis Humaeroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze students' difficulties in managing time between academic learning activities and dormitory activities at Madrasah Ibtidaiyah Ma’had Al-Zaytun. Time management is an essential skill for students in boarding school systems because they are required to balance structured academic and non-academic activities. However, not all students have adequate time management skills, which may affect their learning readiness and academic performance. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, semi-structured interviews, and documentation involving fifth-grade students, homeroom teachers, and dormitory supervisors. The results showed that students experienced several difficulties, including limited ability to divide time effectively, difficulty determining activity priorities, physical fatigue due to dense daily schedules, and limited use of free time for independent learning. These difficulties were influenced by internal factors such as learning motivation and self-regulation ability, as well as external factors such as structured dormitory schedules and environmental demands. Students attempted to overcome these challenges by setting priorities, utilizing spare time for studying, and seeking guidance from dormitory supervisors. The study concludes that time management skills play an important role in supporting students’ academic readiness and character development in boarding school environments. Therefore, strengthening time management guidance through structured mentoring and character education programs is necessary to support students’ academic and personal development.